Inscribed versus Invoked Attitudes: Appraisal Among Indonesian Teenagers in English Captions on Instagram - Dian Rivia Himmawati; Aris Munandar; Sajarwa Sajarwa (Master Program in Linguistics, Diponegoro University, 2022)
On Instagram, Teenagers’ captions in English do not always describe the picture but symbolically express their feelings to their friends as a whole. In this case, English captions enhance status and authority and reveal the attitudinal evaluation related to feelings and values. This paper aims to discuss the self-presentation between Indonesian female and male teenagers on their emotional, critical and evaluative stance reflecting on English captions on Instagram when the captions talk about friends and their relationship. Appraisal theory proposed by Martin and White to reveal the attitudinal evaluation is applied in this study. From 500 English captions, 90 captions deal with 155 appraising items about friends. They are 112 female appraised items and 43 male appraised items. Caption's screenshots are used to collect the data. The invoked attitude data are coded by examining posted photos. The result of the research is (1) male and female teenagers prefer to express their attitude by using inscribed attitude rather than invoked attitude, (2) male teenagers expresses moreattitude through Affect, while female teenagers express more through Judgment, (3) negative appraisal is to used to emphasize the positive values in the form of a counter concession, for male teenagers to highlight togetherness, while for female teenagers are more focused on empathy, (4) both female teenagers and male teenagers use negation to show a positive attitude related to judgment propriety (ethical Judgment). Therefore, writing captions on Instagram provide an opportunity for male and female teenagers to express their attitudes as they imagine to show their strength without physically confronting the interlocutor.